Cuando la creación de un consorcio proporciona respuestas útiles: experiencia de la Latin American DILI network (LATINDILIN). (29th May 2019) - Bessone, Fernando; Hernández, Nelia; Mendizábal, Manuel; Sánchez, Adriana; Paraná, Raymundo; Arrese, Marco; Tagle, Martín; Girala, Marcos; Lizarzábal, Maribel; Carrera, Enrique; Brahm, Javier; Contreras, Fernando; et al.
Abstract : Watch a video presentation of this article Watch the interview with the author (English) Watch the interview with the author (Spanish)